Reinterpretacja prymatu biskupa Rzymu w kontekście współczesnej debaty o synodalności - Krupka, Aneta (Verbum Vitae, 2023)
The article discusses the reinterpretation of the understanding of the primacy of the Bishop of Rome in the context of the contemporary debate about synodality. Firstly, selected historical arguments are used for a strictly ecclesiastical interpretation of primacy. Secondly, the primatial theology of First Vatican Council is discussed. Thirdly, the reception of the definition of primacy and infallibility is described, with particular emphasis on the concept of collegiality. Finally, it is shown how the contemporary synodality debate presents a concrete challenge to the understanding of primacy. The analysis of historical sources and the Magisterium of the Church leads to the conclusion that the synodality of the Church also requires a more ecclesial view of primacy. The role of the Bishop of Rome can be fully understood only by taking into account his deep ecclesial roots as a servant of the of the Church unity. Contemporary Church documents express this concept through the related vision of primacy (the Bishop of Rome), collegiality (the bishops) and synodality (the people of God).